Paul Diederich and the progressive American high school - Hampel, Robert L. (Readings in educational thought., 2014)
Paul Diederich worked in five new organizations dedicated to transforming American schools: the Ohio State University lab school, the Eight Year Study, a Harvard institute to revamp English language instruction, the University of Chicago's Board of Examiners, and the Educational Testing Service. Throughout his career he wrote critiques of American high schools and set forth many proposals to make them more flexible without sacrificing academic excellence. This anthology resurrects 14 Diederich essays, eight of them never before published. The scope ranges from visions of social justice to the details of the daily schedule. Like his heroes Benjamin Franklin and Thomas Jefferson, he combined a passion for utopian speculation with a fascination for practical problems, a combination that is rare in the world of school reform today.